1981
DOI: 10.1177/019459988108900609
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Correction of Anatomic Abnormalities in Obstructive Sleep Apnea Syndrome: Uvulopalatopharyngoplasty

Abstract: Excessive daytime sleepiness and loud snoring are the major symptoms of obstructive sleep apnea, often leading to serious medical complications if unrecognized and untreated. Tracheostomy has been the only effective treatment in most adult cases. This paper reports on a new surgical approach to treat obstructive sleep apnea by uvulopalatopharyngoplasty designed to enlarge the potential airspace in the oropharynx. Twelve patients underwent this operation. In nine there was relief of symptoms and in eight there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
509
1
27

Year Published

1983
1983
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,108 publications
(539 citation statements)
references
References 11 publications
2
509
1
27
Order By: Relevance
“…However, no diagnostic method is capable of predicting correctly its success, being considered effective only in 50% of the cases 18,[20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…However, no diagnostic method is capable of predicting correctly its success, being considered effective only in 50% of the cases 18,[20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…UPPP can alleviate obstruction, but can seldom eliminate it, and its efficacy rate is reported to be about 50% 5) . However, it is suggested that the rate may be higher if the procedure is performed after the site of obstruction in the upper respiratory tract is meticulously identified 16) .…”
Section: Discussionmentioning
confidence: 99%
“…Uvulopalatopharyngoplasty (UPPP) was first described by Fujita et al [26]. Presently, UPPP is the most widely performed surgery for the treatment of OSA in adults [10,27].…”
Section: Surgeries Of the Oropharynxmentioning
confidence: 99%